The artemisinin-induced dormant stages of Plasmodium falciparum exhibit hallmarks of cellular quiescence/senescence and drug resilience - Tripathi, Jaishree (2024)
Recrudescent infections with the human malaria parasite, Plasmodium falciparum, presented traditionally the major setback of artemisinin-based monotherapies. Although the introduction of artemisinin combination therapies (ACT) largely solved the problem, the ability of artemisinin to induce dormant parasites still poses an obstacle for current as well as future malaria chemotherapeutics. Here, we use a laboratory model for induction of dormant P. falciparum parasites and characterize their transcriptome, drug sensitivity profile, and cellular ultrastructure. We show that P. falciparum dormancy requires a ~ 5-day maturation process during which the genome-wide gene expression pattern gradually transitions from the ring-like state to a unique form. The transcriptome of the mature dormant stage carries hallmarks of both cellular quiescence and senescence, with downregulation of most cellular functions associated with growth and development and upregulation of selected metabolic functions and DNA repair. Moreover, the P. falciparum dormant stage is considerably more resistant to antimalaria drugs compared to the fast-growing asexual stages. Finally, the irregular cellular ultrastructure further suggests unique properties of this developmental stage of the P. falciparum life cycle that should be taken into consideration by malaria control strategies.